THE INFLUENCE OF PRODUCT QUALITY, CELEBRITY ENDORSER, BRAND IMAGE ON PURCHASE DECISION LOCAL SKINCARE PRODUCTS SCARLETT WHITENING IN LHOKSEUMAWE CITY - Irsyah Akhirunanda; Siti Maimunah; Syamsul Bahri; Widyana Verawaty Siregar (RADJA PUBLIKA, 2024)
This research aims to determine the influence of product quality, celebrity endorser, brand image on purchase decision local skincare products Scarlett Whitening in Lhokseumawe City. This type of research uses quantitative research methods. Data was collected using a questionnaire distributed to respondents with a scoring technique using an ordinal scale. The sampling technique in this research used a non-probability sampling technique with an accidental sampling method. The research was conducted on 100 samples of respondents using Scarlett Whitening in Lhokseumawe City. The data analysis technique used is the multiple linear regression analysis method, instrument testing (validity and reliability), classical assumption testing, hypothesis testing using the SPSS 20 program. The results of this research show that product quality has a positive and significant influence on purchasing decisions for Scarlett Whitening in Lhokseumawe City and brand image also have a positive and significant influence on purchasing decisions for Scarlett Whitening in Lhokseumawe City, while celebrity endorser has a negative and insignificant influence on purchasing decisions for Scarlett Whitening in Lhokseumawe City.